Assessment of enthesitis in ankylosing spondylitis by power Doppler ultrasonography - Kiris, Adem; Kaya, Arzu; Ozgocmen, Salih; Kocakoc, Ercan (Springer, 2006)
Objective: To evaluate the relationship between power Doppler ultrasonography (PDUS) assessment and clinical variables including enthesitis index, pain threshold and disease activity parameters, and to document grey-scale US findings of the 13 entheses examined. Design and patients: A total of 390 entheses were examined in thirty patients with AS, and clinical variables of the Maastricht Ankylosing Spondylitis Enthesitis Index (MASES), anthropometric measurements, disease activity and functional parameters were documented. A total MASES score by palpation (t-PS) and algometric pressure pain threshold (t-PPT) was obtained. Grey scale and PDUS examination of 13 entheses were performed. Grey-scale changes such as altered tendon echogenity, calcification, cortical reactive changes and bursitis were noted, and flow on PDUS was graded semi-quantitatively. Results: Cumulative power Doppler (t-PDS) score significantly correlated with t-PS and t-PPT. Ultimate correlations were found between power Doppler scores and pain, disease activity and disability parameters. Changes in grey scale combined with PDUS were more prevalent in lower-extremity entheses. The intraobserver agreement of flow signal grading was excellent (kappa=0.82). Clinical and sonographic results were concordant for three regions, but were discordant for four regions where tenderness was accepted as the sole clinical manifestation of enthesis. Conclusion: Pain or tenderness is associated with increased vascularity of entheses. Power Doppler US examination of the entheses may be useful and complementary to the clinical evaluation, and further research is needed to assess its role in diagnosis and follow-up of disease course.
Keywords: ankylosing spondylitis; power Doppler ultrasound; enthesitis; pain